Fluorogenic Sensing of Carcinogenic Bisphenol A using Aptamer‐Capped Mesoporous Silica Nanoparticles. Issue 36 (5th June 2017) - Ribes, Àngela; Aznar, Elena; Bernardos, Andrea; Marcos, M. Dolores; Amorós, Pedro; Martínez‐Máñez, Ramón; Sancenón, Félix
Abstract: Mesoporous silica nanoparticles loaded with rhodamine B and capped with a bisphenol A aptamer were used for the selective and sensitive detection of this lethal chemical. The pores of the nanoparticles are selectively opened in the presence of bisphenol A (through its selective coordination with the aptamer) with subsequent rhodamine B delivery. With this capped material a limit of detection as low as 3.5 μm of bisphenol A was measured. Abstract : A new hybrid aptamer‐capped mesoporous silica material has been developed for the selective and sensitive detection of Bisphenol A in water.